Islamic law : the Sharia from Muhammad's time to the present - Janin, Hunt, 1940-; Kahlmeyer, André, 1978- (Jefferson, NC : McFarland & Co., 2007)
"This volume provides assessment of sharia's achievements, shortcomings and future prospects. The Sharia is discussed with respect to Ottoman law, puritanism and jihad. The sharia's relevance to today's events is explored. Among items provided in appendices are a commentary on a Western translation of the concept of jihad and an analysis of the sharia in 29 selected countries"--Provided by publisher.
Fundamentals of Islam -- Traditional Sharia law : obligations to God and to fellow human beings -- The Sharia and its jurists : from the beginnings to Al-Shatibi's legal reforms -- Ottoman law in the golden age of the empire : Suleyman the magnificent -- The Sharia under Wahhabi puritanism and incursions by the West -- The Sharia and jihad -- The Sharia in the world today -- Islamic banking -- The future of Islamic law : reform or retrenchment?.
Includes bibliographical references ( p. 199-204) and index.
Keywords: Islamic law -- History; Jihad